Visualization of ontology evolution using ontodi graph - Lara, André (2017)
Ontologies evolve with the passing of time due to improvements, corrections or changes in requirements that need to be made. In this paper we describe a thesis work aiming at the creation of a visualization technique with the objective of allowing the viewer to easily identify changes made in an ontology. With the use of a specification based on the already existing Visual Notation for OWL Ontologies (VOWL) it is possible to display the differences that exist between two versions of an ontology. The proposed approach will be implemented in an application, that is also discussed in the paper.